SWOT Analysis in the Implementation of Cosmetic Product Excellence Strategy at PT XYZ to Face the Digital Era - Safira Ramadhanitya; Hapzi Ali (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
This study aims to develop a product excellence strategy that is suitable for PT XYZ, a prominent halal cosmetics distributor in Indonesia, in responding to the dynamics of opportunities and challenges in the digital era. With a descriptive qualitative method based on literature studies, a SWOT analysis was conducted to explore the strengths, weaknesses, opportunities, and threats that affect the company. The findings show that PT XYZ's strength lies in product quality, strong halal brand image, and wide distribution reach. Despite this, the company still faces limitations in terms of digital innovation and expansion into international markets. The growth of e-commerce, the growing interest in natural products, and the potential for digital cooperation are strategic opportunities, while challenges arise from the intensity of competition, changing consumer preferences, and data protection issues. Recommended strategies include accelerating digital transformation, improving online brand image, sustainable product innovation, and partnerships with digital figures. It is hoped that the implementation of this strategy can strengthen PT XYZ's competitive position at the national and global levels in a sustainable manner.